Evaluación de la contaminación del aire por hongos ambientales en los museos de la ciudad de Iquitos. Loreto, Perú-2022 - Dominguez Mieses, Brayan Fidel (2022)
The city of Iquitos exhibits its history through its museums, where we find paintings, photo frames, wood, statues, handicrafts, which are damaged by fungi and constitute a health risk; Therefore, the present research work was developed between the months of september to december 2021, with the objective of evaluating air pollution by environmental fungi in the museums of the city of Iquitos. The research was descriptive, longitudinal and quantitative. The gravimetric method of plate sedimentation with potato dextrose agar was used, incubating at room temperature for 4 or 5 days. The macroscopic identification was carried out observing the characteristics of the colonies and for the microscopic identification the humid chamber technique was used, taxonomic keys were used. In the present investigation, 519 colonies of environmental fungi were obtained, 180 colonies in the Mi Iquitos Museum and 339 in the Iquitos Amazon Museum; Sterile mycelium was the fungus with the highest relative density (33.91%), followed by Yeast (25.43%), Penicillium sp (12.72%) and with the lowest density were Rhizopus sp, Pestalotia sp and Aspergillus terreus (0.19%). In the scale of contamination degrees, the Iquitos Amazon Museum obtained the category of high contamination with 1117 cfu/m3, while the Mi Iquitos Museum obtained 288 cfu/m3 corresponding to the intermediate category of contamination. Temperatures ranged between 27°C - 29°C and ambient humidity was between 80% and 58%.